Utilization of Antenatal Care in Primary Health Centers in Mosul City - Thanoon Mohammed Thanoon (College of Nursing,University of Mosul, 2015)
Background and aim: most women enter pregnancy period in apparent good health and achieve a normal pregnancy, and birth without complications. For a few women, however, suffer in the course of the pregnancy for reasons that are usually unclear antenatal care aims at preventing complications. The study aims to utilize health care services for pregnant women in primary health centers. Materials and method: a cross sectional study was conducted and adopted in Al - Quds and Al - Hadbaa' primary health care centers, the data started to be gathered from 1st of Jan 2010 - 10th March 2011. To achieve the adjectives of the study, Accidently sample consist from (400) pregnant women were selected, the data were collected through using constructed checklistwhich consist from four parts ,the first is dealing with the pregnant information registration that include (5 item) , the second part is related to laboratory test which consist of (12 item), while the third part is about health education which include (13 items) and finally the last part is dealing with high risk problem that consist of (8 items). The validity and reliability test was done to ensure the consistency of study tool which the correlation coefficient is (86.4) with standard deviation about ( 0.43). Results: the results of the study indicated the health services that introduce to pregnant women who attending to primary health care centers is applied in these centers ,the implementation of chart is highly performance with some variance of some result that related to investigation property and availability, finally the differences between two centers show significance by the health education in dealing with risk factor. Conclusion: the present study concluded that there is a good implementing almost all aspects of the pregnant women health services management. Recommendation: the researcher can conclude that the utilization of the pregnant women chart and application in strict way had the high impact on preventing pre and antenatal problem in pregnancy and training practice on it. Keywords: pregnant women, health services, primary health care centers